Mild and Moderate Extraction Methods to Assess Potentially Available Soil Organic Nitrogen - Braos, Bruno Boscov [UNESP]; Ferreira, Manoel Evaristo [UNESP]; Pessoa da Cruz, Mara Cristina [UNESP]; Braos, Lucas Boscov [UNESP]; Barbosa, Jose Carlos [UNESP] (Soc Brasileira De Ciencia Do Solo, 2016)
The use of chemical methods to assess the soil organic nitrogen (N) potentially available to plants is not a common practice in Brazil. However, associated with others, this tool might improve efficiency in the use of waste and nitrogen fertilizers. In our study, chemical methods were tested to assess potentially available soil N in samples of 17 representative soils of the western plateau of the state of Sao Paulo (10 Oxisols and 7 Ultisols). Available soil N was extracted from the collected soil samples using moderate (ISNT-Illinois Soil Nitrogen Test) and mild (hot water and heated solutions of 2 mol L-1 KCl and 0.01 mol L-1 CaCl2) extraction methods. The levels of potentially available N obtained from these chemical methods were correlated with dry matter (DM) and N uptake (N-up) by corn plants grown in pots in a greenhouse experiment carried out with the same 17 soil samples. The ISNT method showed the highest available N extraction capacity, whereas hot water showed the lowest capacity, followed closely by the hot 0.01 mol L-1 CaCl2 solution. Despite the differences among the quantities of available N extracted, the methods correlated with each other and with DM and N-up, but the values from the ISNT method showed the lowest correlation with plant variables (r(DM) = 0.67** and r(Nup) = 0.81**). Procedures of extraction with water or 0.01 mol L-1 CaCl2 heated for 16 h, and 2 mol L-1 KCl heated for 4 h, resulted in similar correlation values (r) with plant DM and N-up. Thus, water (r(DM) = 0.77** and r(Nup) = 0.90**) and 0.01 mol L-1 CaCl2 (r(DM) = 0.82** and r(Nup) = 0.93**) heated for 16 h can be recommended as the best options for N extraction. considering the possibility for predicting N availability, lower generation of waste, and lower cost of analysis.
Keywords: chemical analysis; organic matter; mineralization